Evaluation of Factors Affecting the Innovation Index and Its Synergistic Effects on Economic Growth in Selected Countries - Hatem Hammood Alowaidi , Khitam; Ghobadi, Sara; Kadhim Abd Al-Bakri, Jawad; Sharifi Ranani, Hussein (Business, Marketing, and Finance Open, 2026)
Innovation is the most powerful tool for strengthening national competitiveness in the global economy, and its importance is such that a large part of countries’ development is assessed based on their scientific and technological achievements. Accordingly, the present study evaluates the factors influencing innovation, as well as the impact of innovation on economic growth, within the framework of two equations estimated simultaneously during the period 2015–2024 in a set of selected upper-middle-income countries. To estimate the research model, the study employed the system panel data approach using the Generalized Method of Moments (GMM). The findings, at a 95% confidence level, indicate that improvements in global value storage, institutional factors, network readiness, and protection of individual property rights positively affect innovation in the selected countries. Furthermore, the results reveal that improvements in global competitiveness, business environment, economic complexity, and innovation contribute to the increase of economic growth.